2023
DOI: 10.1097/mog.0000000000000929
|View full text |Cite
|
Sign up to set email alerts
|

The debate in the diagnosis of coeliac disease – time to go ‘no-biopsy’?

Abstract: Purpose of review Duodenal biopsies have been central to making a diagnosis of coeliac disease for the last 70 years. Recent paediatric guidelines have reduced the emphasis on duodenal biopsies with the incorporation of a ‘no-biopsy’ arm to the diagnostic pathway. This review discusses the no-biopsy approach in adults and highlights advances in alternative (non-biopsy) diagnostic modalities in coeliac disease. Recent findings Evidence suggests that a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…This no-biopsy approach has been used in the paediatric population for over a decade ( 56 ). Yet, following the same approach to diagnose adults with CD has been a matter of an ongoing debate ( 57 , 58 ). Avoiding unnecessary endoscopy could lead to significant reductions in both the healthcare costs and the carbon footprint of endoscopy ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…This no-biopsy approach has been used in the paediatric population for over a decade ( 56 ). Yet, following the same approach to diagnose adults with CD has been a matter of an ongoing debate ( 57 , 58 ). Avoiding unnecessary endoscopy could lead to significant reductions in both the healthcare costs and the carbon footprint of endoscopy ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…More evidence may be needed to inform guidance relevant to primary care as current evidence for a no-biopsy approach is from secondary and tertiary care settings with a significantly higher prevalence of CD than you would expect in primary care. 6 , 9 , 18 If future evidence supports that diagnosis of certain cases is transferred into primary care, healthcare professionals would have to be competent discussing accuracy of serological tests in order to empower patients to feel confident in their diagnosis and commitment to a life-long GFD. Appropriate follow up must also be available, including referral to a dietitian for all patients and referral to a gastroenterology specialist for those with lingering symptoms.…”
Section: Impact On Primary Carementioning
confidence: 99%
“… 4 , 5 There is variability in adherence to these guidelines in practice and clinical pathways are evolving. 6 …”
Section: Introductionmentioning
confidence: 99%
“…While the "no-biopsy pathway" of making a diagnosis is getting popular among pediatricians and pediatric gastroenterologists, most professional guidelines for the diagnosis of CeD in adults still recommend the demonstration of villous abnormalities in addition to presence of IgA anti-tTG Ab. 5 In recent times, many investigators have shown interest in exploring the prediction of villous abnormalities of modified Marsh grade 3 with high titers of IgA anti-tTG Ab. In a multicenter study including 1417 adult patients with CeD, 431/1417 (30%) had anti-tTG Ab titers ≥10-fold, of which 424 (98%) had villous abnormalities of modified Marsh grade 3 on duodenal biopsy.…”
Section: Introductionmentioning
confidence: 99%